Feasibility Analysis of Inquiry-Based Learning DesignSocio-Scientific Issues (SSI) to Improve Students' Halal Literacy and Critical Thinking Skills on Additives and Addictive Substances - Laeli Kurmatillah; Chaerul Rochman; Nurhayati Nurhayati (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the feasibility of an inquiry-based Socio-Scientific Issues (SSI) learning design developed to enhance halal literacy and critical thinking skills among junior high school students on the topic of additives and addictive substances. The research employed a descriptive quantitative approach with a Research and Development (R&D) method, focusing on the product validation stage. Data were collected through validation sheets completed by three expert validators, covering 11 assessment components with a total of 57 aspects. The data were analyzed by calculating the feasibility percentage of each component. The validation results indicated an average feasibility score of 97.6%, categorized as excellent. These findings suggest that the developed learning design meets the criteria of content completeness, clarity of objectives, appropriateness of approach, and assessment feasibility, making it suitable for implementation in subsequent learning stages.